Gaining Tacit Knowledge from Foreign Buyers: The Role of Prior Knowledge, Business Relatedness and Interactive Involvement - MdSaad, Norsafinas; Ghauri, Pervez N.; Jedin, Mohd Haniff (International Journal of Supply Chain Management, 2016)
As competition has become increasingly knowledge-based, firms must double their efforts to increase their competitiveness by integrating the existing knowledge with new and updated knowledge resources, which maybe acquired through various approaches. One of the most popular strategies for knowledge acquisition is through strategic alliance, which can take the form of international outsourcing or another contractual agreement. As a result of the rising trend of international outsourcing and strategic value of tacit knowledge, this paper aims to provide a conceptual perspective on the importance of business relatedness and interactive involvement in the acquisition of tacit knowledge from the international suppliers’ point of view.